Improving Dayaknese-Speaking Learners’ English Pronunciation - Ristati; I Nyoman Suparwa; I Nengah Sudipa; Ni Made Dhanawaty (e-Journal of Linguistics, 2019)
The L1 influence causes difficulties for Dayaknese-speaking leaners (hereinafterreferred to as learners) of English in producing English sounds. In English, pronunciation playsimportant role to understand the communication. The purposes of learning English pronunciationfor learners are (1) able to communicate in English clearly and intelligibly, (2) able to get themeaning of information conveyed in real life situations, (3) able to improve self-confidencewhile communicating oral English, and (4) able to monitor the use of English (able to listen,understand, and produce). The teaching of English subject in Indonesian schools includes fourskills, namely listening, speaking, reading, and writing. While linguistic elements, such asvocabulary, grammar, pronunciation, and cultural patterns of discourse are the supporters ofthese four skills.This current research aimed to describe the implementation of behaviorism learning method andcommunicative approach as an attempt to improve English pronunciation for learners. Thiscurrent research was conducted by means of Research and Development (R & D) design,employing the stages as follows: analysis, design, development, implementation, and evaluation.Testing was done with experiment, which compares the effectiveness between the old(conventional) learning method and the new method (behaviorism learning method with acommunicative approach). The indicators of the effectiveness of new method were the speed ofthe learners’ understanding, the learners’ creativity, and the learners’ learning outcomes.Experiment was carried out by comparing with previous condition and after using a new learningmethod (before-after) or also called one group pretest-posttest. Based on statistical count, t count= -34.37 and t table = 1.67, the value of t count falls on Ha acceptance area (new learningmethod was more effective than conventional learning method) or Ha was accepted and Ho wasrejected.